INTEGRATING ISLAMIC VALUES INTO THE DEVELOPMENT OF ORDERING, INVITATION, AND ASKING FOR PERMISSION UNIT - Nur Aliyah Nur; Annisa Shofa Tsuraya; Rifqa Reskiawati (Univeristas Islam Negeri (UIN) Alauddin Makassar, 2022)
This research was conducted to develop English teaching materials for students based on the 2013 curriculum, especially on basic competencies 3.4 and 4.4 about Ordering, Invitation, and Asking for Permission, for the eighth-grade students at MTs Madani Pao-Pao. The researchers used R&D with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The types of data collection in this research were quantitative and qualitative. The researchers used questionnaires for students as instrument and used validation sheet for experts. The results indicated that the students' needs for English material of Ordering, Invitation and Asking for Permission unit are different, starting from the material organization, the content of the material and the characteristics of students. The English material used in madrasah is still general and it is not integrated with Islamic values. Therefore,